Cu66 nanoclusters from hierarchical square motifs: Synthesis, assembly, and catalysis - Xueli Sun; Yuchen Wang; Qingyuan Wu; Ying‐Zi Han; Xuekun Gong; Xiongkai Tang; Christine M. Aikens; Hui Shen; Nanfeng Zheng (Aggregate)
Abstract The elucidation of hierarchical assembly structure of metal nanoclusters is of fundamental importance in the context of bottom‐up fabrication and functionalization. While recent studies have provided valuable insights into the multiscale assembly patterns of gold or silver‐based nanoclusters, the success in achieving similar results for copper analogues has been notably limited. Herein, by virtue of a slow‐ligand‐release strategy, a copper nanocluster denoted as [Cu66Cl8(PPh3)8(SC2H5)32H24](SbF6)2 was synthesized, resulting in the formation of fresh hierarchical assembly structures in one‐pot. The arrangement of the metal atoms within the cluster reveals an orderly of 16 Cu4 squares, representing a rare copper nanocluster comprising square motifs. Additionally, the ligands (phosphine, thiolate, and halide) coordinate to the surface of the cluster in a regiospecific manner, displaying square patterns as well. The self‐assembly facilitated by the C‐H···F interaction between the cluster moieties and SbF6− anions further induces the formation of three‐dimensional cubes and eventually large nanocrystals. Density functional theoretical (DFT) calculations reveal that hydride atoms with low chemical shifts typically exhibit short Cu‐H distances. The cluster demonstrates moderate stability and high catalytic activity in the chemoselective hydrogenation of cyclohexanone under mild conditions.